Analisis Sistem Rekrutmen, Seleksi Dan Penempatan Posisi Kerja Tehadap Kualitas Kinerja Karyawan (Studi Kasus Pada PT. Indra Karya Persero Divisi Engineering 1 Malang) - Fatchur Rohman Bayhaqy; Siti Asiyah; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the implementation of the system of recruitment, selection, and placement of work positions on the quality of employee performance which focuses on improving the quality of performance. This research was conducted at the company PT. Indra Karya Persero Division Engineer 1, Klojen Subdistrict, Malang City. This research is a qualitative descriptive study. Data collection techniques using interviews, observation and documentation studies. The data analysis technique of this research used a qualitative descriptive analysis approach. Human resource planning consists of, recruitment, selection, and placement of work positions. The strategy carried out by PT. Indra Karya Persero Division Engineer 1 Malang observes the effectiveness of recruitment, selection, and job placement in order to provide quality human resources to the company. Thus it becomes important to improve human resources, namely the target of improving the quality of employee performance. Keywords : Recruitment System, Selection, Job Placement, Performance Quality